Delayed but not derailed: legislative compliance with European Court of Human Rights judgments. Issue 8 (14th September 2019) - Stiansen, Øyvind
ABSTRACT: Legislative changes can be crucial for implementing human rights. This article investigates how the need for legislative changes influences compliance with European Court of Human Rights (ECtHR) judgments. I argue that the need for legislative changes might influence compliance politics in two ways. First, ECtHR interference with the will of elected parliaments is controversial in several European states. Such controversy might increase the risk of defiance of judgments requiring legislative changes. Second, the greater number of veto players needed to pass legislative is likely to delay compliance. Using original implementation data, I show that the need for legislative changes tends to delay compliance, but does not increase the risk of long-term defiance. The ECtHR's ability to eventually prompt legislative changes is not smaller than its ability to induce other reforms. I also find that delays associated with the need for legislative changes are greater in states with greater numbers of ideologically diverse veto players, in states with a proportional electoral system, and in states without domestic judicial review.